Dynamics of Bangladesh-India relations : dialogue of young journalists across the border - Sobhan, Farooq (The University Press, 2005)
Contributed articles on Bangladesh relations with India presented at two Bangladesh-India Dialogue for Young Journalists on September 7-8 and November 30th-December 1st 2004.